Acupuncture for Hot Flashes in Cancer Patients: Clinical Characteristics and Traditional Chinese Medicine Diagnosis as Predictors of Treatment Response. (May 2019) - Liu, Wenli; Qdaisat, Aiham; Lopez, Gabriel; Narayanan, Santhosshi; Underwood, Susan; Spano, Michael; Reddy, Akhila; Guo, Ying; Zhou, Shouhao; Yeung, Sai-Ching; Bruera, Eduardo; Garcia, M. Kay; et al.
Background: Acupuncture is a recognized integrative modality for managing hot flashes. However, data regarding predictors for response to acupuncture in cancer patients experiencing hot flashes are limited. We explored associations between patient characteristics, including traditional Chinese medicine (TCM) diagnosis, and treatment response among cancer patients who received acupuncture for management of hot flashes.Methods: We reviewed acupuncture records of cancer outpatients with the primary reason for referral listed as hot flashes who were treated from March 2016 to April 2018. Treatment response was assessed using the hot flashes score within a modified Edmonton Symptom Assessment Scale (0-10 scale) administered immediately before and after each acupuncture treatment. Correlations between TCM diagnosis, individual patient characteristics, and treatment response were analyzed.Results: The final analysis included 558 acupuncture records (151 patients). The majority of patients were female (90%), and 66% had breast cancer. The median treatment response was a 25% reduction in the hot flashes score. The most frequent TCM diagnosis was qi stagnation (80%) followed by blood stagnation (57%). Older age ( P = .018), patient self-reported anxiety level ( P = .056), and presence of damp accumulation in TCM diagnosis ( P = .047) were correlated with greater hot flashes score reduction.Conclusions: TCM diagnosis and other patient characteristics were predictors of treatment response to acupuncture for hot flashes in cancer patients. Future research is needed to further explore predictors that could help tailor acupuncture treatments for these patients.